The Impact of Supply Chain Management Practices on Competitive Advantage and Organizational Performance - Roland Y. H. Silitonga; Marla Setiawati; Sarah E. K. Immanuella (The Indonesian Institute of Science and Technology Research, 2023)
This study aims to examine the effect of supply chain management (SCM) on competitive advantage and company performance in the MSME culinary industry in Bandung. The subject of this research is the culinary industry MSMEs in the city of Bandung. This type of research is quantitative research using a questionnaire distributed directly to the culinary industry, with as many as 40 questionnaires. Data analysis used multiple linear regression and path analysis. The results show that supply chain management influences competitive advantage, supply chain management is not proven to affect company performance, competitive advantage affects company performance, and supply chain management affects company performance through competitive advantage but tends to have an influence—direct effect on company performance.